Typhoon Merbok induced upwelling impact on material transport in the coastal northern South China Sea. - Chen Jiang; Ruixue Cao; Qibin Lao; Fajin Chen; Shuwen Zhang; Peiwang Bian (PLoS ONE, 2020)
Typhoons frequently affect the South China Sea (SCS), playing an important role in changing the coastal marine system. To determine which process has the greatest impact on material transport in the coastal marine area during a typhoon, the sea temperature, salinity, concentration of nutrients, chlorophyll-a, total suspended matter, and δ13C of particulate organic carbon (δ13C-POC) in the water column of coastal Northern SCS (NSCS) were measured during two cruises in June 2017, in the pre- and post-typhoon Merbok periods. The results show that all parameters changed significantly between the two periods. During the pre-typhoon period, stratification of nutrients and physicochemical parameters, combined to high nutrient concentrations, high temperature, and low salinity in the water column of the nearshore area, suggests that the nearshore area is influenced by the river diluted water originated in the coastal cities adjacent to our study area. In the offshore area, mineralization may be responsible for the high nutrient concentration in the bottom water. However, during the post-typhoon, the stratification of nutrients is less significant and their distribution more homogenous in the whole water column of the nearshore area. In the upper water, the nutrient concentration increased and the temperature decreased significantly. These results suggest that the enhanced vertical mixing induced by the typhoon was the dominant process in changing the nutrient distribution pattern in the coastal NSCS.